Medicamentos anti-hipertensivos na gestação e puerpério - Siqueira, Fábio; Moura, Thiago Rocha; Silva, Sulani Souza; Peraçoli, José Carlos [UNESP] (My University, 2011)
Pregnancy toxemia is a multisystemic disease, which occurs mainly at the end of pregnancy, characterized by clinical manifestations such as hypertension, edema and proteinuria. It is the most commonly occurred medical complication in pregnancies and the main cause for perinatal and maternal morbimortalities. The purpose of this article is to review the main aspects concerning the use of antihypertensive agents during pregnancy and puerperium. The data has been collected from Pubmed and Bireme, from 2006 to 2010 using the words “anti-hipertensivo e gravidez” and “antihypertensive and pregnancy”. The knowledge regarding hypertension during pregnancy and its therapy is evolving; the search for medication that could protect the mother from acute dangers and to ensure a healthy newborn must be the focus. Evidence is still lacking regarding the best therapy, beginning period, duration and results. In spite of the pharmacological advances, there are still no drugs completely exempt of compromises to the mother and the conceptus.

A toxemia gravídica é uma doença multissistêmica, que ocorre principalmente no final da gravidez, caracterizada por manifestações clínicas como hipertensão, edema e proteinúria. É a complicação médica mais comum da gravidez e a principal causa de morbimortlidade materna e perinatal. O objetivo deste artigo é rever os principais aspectos concernentes ao uso de agentes antihipertensivos na gravidez e puerpério. Os dados foram coletados no Pubmed e Bireme, período de 2006 a 2010 utilizando-se os descritores “anti-hipertensivo e gravidez” e “antihypertensive and pregnancy”. O conhecimento da hipertensão durante a gestação e sua terapêutica está em evolução; a busca por medicações que possam proteger a mãe dos perigos agudos e garantir um recém nascido saudável deve ser o foco. Faltam evidências sobre a melhor terapia a ser adotada, período de início, duração e resultados. Apesar do avanço farmacológico, ainda não há fármacos totalmente isentos de comprometimento para a mãe e ao concepto.
Antihypertensive medications in pregnancy and puerperium
Keywords: Hypertension; Pregnancy toxemia; Antihypertensive; Preeclampsia; Hipertensão; Toxemia gravídica; Anti-hipertensivos; Pré-eclampsia